Barriers to green buildings at two Brazilian engineering schools - Kasai, Nayara; Jabbour, Charbel José Chiappetta [UNESP] (Elsevier, 2014)
The objective of this short communication is to identify and analyze the main barriers to the adoption of green buildings at two traditional Schools/Colleges of Engineering in the state of São Paulo, Brazil. The methodological process employed is the multiple case studies used to diagnose the main barriers to installing green buildings in these two cases. The intention, of the institutions, to adopt greener buildings has been observed, considering the commitment of top management and that the institutions have put forth to accelerate this greening process. However, the barriers to adoption are evident, especially those of a technical and cultural origin. Based on these results, the study proposes possible solutions and guidelines to overcome such barriers, aimed at facilitating the adoption of green technologies in the buildings at Higher Education Institutions (HEIs)/Schools/Colleges of Engineering.
Keywords: Green buildings; School/College of Engineering; Environmental management; Higher Education Institutions; Energy saving